2017
DOI: 10.1002/dvdy.24493
|View full text |Cite
|
Sign up to set email alerts
|

Upstream regulation for initiation of restricted Shh expression in the chick limb bud

Abstract: Taken together with results of functional assays, we propose a model in which positive and negative transcriptional regulatory networks accumulate their functions in the intersection area of their expression regions to provide a restricted spot for the ZPA, the source of morphogen, Shh. Developmental Dynamics 246:417-430, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 111 publications
(153 reference statements)
0
8
0
Order By: Relevance
“…Using an antisense-probe (~1000 bp) that was a gift from the Tanaka lab (IMP, Austria), we determined that Shh was first expressed at stage 45 in a posteriorly restricted domain and persisted through stage 49 in a posterior-proximal position (Figure 2A). Compared to anuran and other amniote forelimb buds where Shh expression precedes expression of Hoxd11 , the onset of Shh expression in axolotls appeared relatively late and after Hoxd11 expression (Matsubara et al, 2017; Riddle et al, 1993) (Figure 2—figure supplement 2). While the posterior Shh expression pattern was consistent with previous reports using relatively short probes at several stages (Bickelmann et al, 2018; Imokawa and Yoshizato, 1997; Torok et al, 1999), we also observed Shh expression in an anteriorly restricted domain at stages 46, 47 and 48 (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an antisense-probe (~1000 bp) that was a gift from the Tanaka lab (IMP, Austria), we determined that Shh was first expressed at stage 45 in a posteriorly restricted domain and persisted through stage 49 in a posterior-proximal position (Figure 2A). Compared to anuran and other amniote forelimb buds where Shh expression precedes expression of Hoxd11 , the onset of Shh expression in axolotls appeared relatively late and after Hoxd11 expression (Matsubara et al, 2017; Riddle et al, 1993) (Figure 2—figure supplement 2). While the posterior Shh expression pattern was consistent with previous reports using relatively short probes at several stages (Bickelmann et al, 2018; Imokawa and Yoshizato, 1997; Torok et al, 1999), we also observed Shh expression in an anteriorly restricted domain at stages 46, 47 and 48 (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Second, salamander forelimb buds exhibit a proximal-anterior domain of Shh expression that emerges as the axolotl limb bud begins to bend posteriorly; a domain which is not found during normal limb development in amniotes and anurans. Third, posterior Shh expression corresponding to the ZPA remains in a relatively small proximal domain (Torok et al, 1999) rather than the elongated expression domain found in other tetrapods that extends the proximal-distal length of the autopod (Matsubara et al, 2017; Riddle et al, 1993; Shapiro et al, 2003). With respect to the first point, previous work has demonstrated that flank tissue surrounding the limb field plays an important role in specifying the anteroposterior axis and thus, the temporal appearance of Shh expression may be less important than its posterior induction (Stocum and Fallon, 1982).…”
Section: Discussionmentioning
confidence: 95%
“…Several targets known to be upstream of SHH expression, including Homeobox D9 [ 34 , 35 ], ELF2 (a member of the ETS family), and HAND2 (a basic helix–loop–helix transcription factor) were up-regulated 2.3-fold, 1.9-fold, and 1.6-fold, respectively. A complex interaction between HOX, PBX, ETS, and HAND2 has been implicated in the activation and localization of SHH expression to the ZPA [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the feather follicle in the FFF region deeply sinks to the posterior-dorsal surface of the bone. Although the mechanism of epithelial invagination of a feather bud in the FFF region is largely unknown, an interesting report by Lin et al [13] suggested that tubular invagination is achieved through loosening of the bud mesenchyme. Epithelial cell proliferation and elongation in the bud may lead to the formation of a sprout that invades the surrounding loosened mesenchyme, and epithelial-mesenchymal interaction may contribute to the epithelium organization as seen in the morphogenesis of other types of epithelial tissues such as mammary glands [25].…”
Section: Discussionmentioning
confidence: 99%
“…Forelimb buds and a square of abdominal skin with hypodermal tissues were excised from staged chicken embryos and processed for whole-mount in situ hybridization as described previously [12] using antisense RNA probes for chick shh (see [12, 13] for detailed information of shh RNA probes). In the later stages of feather morphogenesis, shh is expressed in the marginal plate epithelium that will undergo cell death, providing spaces between the barbs [1416].…”
Section: Methodsmentioning
confidence: 99%